Rebuilding Soil Ecosystems for Improved Productivity in Biosolarized Soils - Laura Ney; Dorcas Franklin; Kishan Mahmud; Miguel Cabrera; Dennis Hancock; Mussie Habteselassie; Quint Newcomer; Brendan Fatzinger (International Journal of Agronomy)
Disinfecting soil can reduce or eliminate crop loss from soilborne pathogens, parasitic nematodes, and weed competition. Biosolarization combines biotoxic products from organic matter decomposition and heat from solarization. While biosolarization offers an organic option for soil pest control and avoids human and environmental health risks associated with chemical fumigants, it still has broad negative impacts on microbial communities. Quickly reestablishing these communities can be key in preventing resurgence in disease pressure and in maximizing nutrient use efficiency. The objective of this study was to determine the ability of fertilization source, N fertilization rate, and/or inoculate to rebuild an active soil ecosystem in biosolarized soils by measuring nematode community structure, microbial biomass, and C and N mineralization in soil as well as kale yield and quality. The study was conducted using potted kale grown in biosolarized soils. Treatments were bare soil, receiving no fertilization, and soils receiving two different rates of organic, composted broiler litter or mineral fertilizer. Half of the pots in each treatment received a locally sourced microbial inoculant (LEM). Among the nonfertilized treatments, the soils that received applications of LEM mineralized more nitrogen and produced higher yields. Soils that received the highest rate of compost immobilized the greatest proportion of nitrogen applied, were the most cold-tolerant, and produced the largest yields. None of the kale that received heavy mineral fertilization without LEM inoculation survived a hard freeze; however, the ones that received LEM applications were able to partially recover. We also found that kale grown with lower rates of N (50 kg·ha−1), applied as compost plus LEM, had the greatest magnesium leaf content and were more economically efficient while producing an equally abundant and nutritious food.